An Infrared Luminous Merger with Two Bipolar Molecular Outflows : ALMA View of NGC 3256. Issue Volume 10:Issue S309(2014) (9th February 2015) - Sakamoto, K.; Aalto, S.; Combes, F.; Evans, A.; Peck, A.
Abstract: We found with ALMA 3D spectroscopy two bipolar molecular outflows in the luminous infrared galaxy NGC 3256. Each of the two merger nuclei has its own bipolar outflow.